Assessing the Validity of the MyJump2 App for Measuring Different Jumps in Professional Cerebral Palsy Football Players: An Experimental Study - Coswig, Victor; Silva, Anselmo De Athayde Costa E; Barbalho, Matheus; Faria, Fernando Rosch De; Nogueira, Claudio D; Borges, Mariane; Buratti, Jéssica R; Vieira, Ivaldo B; Román, Francisco Javier López; Gorla, José I (JMIR Publications, 2019)
BackgroundVertical jumps can be used to assess neuromuscular status in sports performance. This is particularly important in Cerebral Palsy Football (CP Football) because players are exposed to high injury risk, but it may be complicated because the gold standard for assessing jump performance is scarce in field evaluation. Thus, field techniques, such as mobile apps, have been proposed as an alternative method for solving this problem. ObjectiveThis study aims to evaluate the reliability of the measures of the MyJump2 app to assess vertical jump performance in professional CP Football. MethodsWe assessed 40 male CP Football athletes (age 28.1 [SD 1.4] years, weight 72.5 [SD 6.2] kg, and height 176 [SD 4.2] cm) through the countermovement jump (CMJ) and squat jump (SJ) using a contact mat. At the same time, we assessed the athletes using the MyJump2 app. ResultsThere were no significant differences between the instruments in SJ height (P=.12) and flight time (P=.15). Additionally, there were no significant differences between the instruments for CMJ in jump height (P=.16) and flight time (P=.13). In addition, it was observed that there were significant and strong intraclass correlations in all SJ variables varying from 0.86 to 0.89 (both P<.001), which was classified as "almost perfect." Similar results were observed in all variables from the CMJ, varying from 0.92 to 0.96 (both P ≤.001). ConclusionsWe conclude that the MyJump2 app presents high validity and reliability for measuring jump height and flight time of the SJ and CMJ in CP Football athletes.